Faktor-Faktor Masyarakat Tetap Tinggal di Kawasan Rawan Bencana Banjir, Desa Dayeuhkolot, Kabupaten Bandung - Adharina, Nabilla Dina; Hakim, Dany Lukmanur (Fakultas Teknik Universitas Bosowa, 2024)
Dayeuhkolot Village is one of the villages in Bandung Regency that is consistently hit by flood disasters. According to data from the Bandung Regency Disaster Management Agency (BPBD) in 2019, there were a total of 41 flood incidents, primarily occurring during periods of heavy rainfall. The recurrent flooding in Dayeuhkolot Village has resulted in significant losses for the local community. Consequently, some residents of Dayeuhkolot Village have chosen to move out, leading to a decline in population growth in the area. Despite the relocation of some residents, others have chosen to remain in Dayeuhkolot Village despite the constant threat of floods during the rainy season. This research investigates the factors influencing residents' decisions to either stay or move away from Dayeuhkolot Village due to the recurring flood disasters. To determine these factors, this study employs logistic regression analysis with independent variables related to environmental quality, services, social factors, accessibility, economics, job opportunities, and land prices. The research findings indicate that the primary factors influencing the residents of Dayeuhkolot Village's decision to stay or move due to floods are environmental quality and the community's economy. Among these two factors, the variable of environmental quality, which encompasses safety, cleanliness, and environmental health, has the most significant impact on residents' preferences.